Early Identification of The Use of Borax And Textile Dye in Ciburial Village, Cimenyan District, Bandung - Riseu Meisani; Moch Yogi Santika Nugraha; Ferli Septi Irwansyah (Gunung Djati Conference Series, 2023)
This counseling was held in Baribis Village, Ciburial Village, because there were many unhealthy people scattered in the stalls and in the market, some even used hazardous materials such as borax. The purpose of this counseling is so that people in the Ciburial Village area know the dangers of additives commonly used in everyday life. The methods used are lectures, questions and answers and demonstrations so that people not only listen to theories but are applicable so they know better how to eat good and reduce the use of additives in everyday life. The result of this outreach is that the public knows how to distinguish between foods that contain synthetic dyes and borax. In textile dyes, it is known by adding detergent, textile dyes when given detergent will change to color, while natural dyes such as dragon fruit when added with detergent will turn darker in color. To find out which foods contain borax, the turmeric test is carried out, when turmeric extract is given to food, a dark brown color change occurs. The use of large amounts of borax can cause kidney damage and even death